Critical Review on Pharmaceutical Prospects of Nagabhasma Incinerated Lead - Rajput, Dr Dhirajsingh Sumersingh (International Journal of Pharmaceutical & Biological Archive, 2015)
Critical Review on Pharmaceutical Prospects of Nagabhasma Incinerated Lead